การพยากรณ์มูลค่าการส่งออกอุตสาหกรรมสิ่งทอของไทย - นวลพรรณ มีนาทุ่ง (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
To find an appropriate statistical methods of forecasting the exports of textile products based on small error. The mean absolute percent error was used as the criterion for choosing between the following four forecasting techniques: Box-Jenkins, exponential smoothing, regression analysis, and decomposition. This study used the following additional data : Gross Domestic Product (GDP) and import data (between 1984 to 1998) from the International Financial Statistics Yearbook 1998, published by the International Monetary Fund (IMF); minimum wages in Bangkok and adjacent provinces from the national statistical office; number of textile machines installed, number of production workers and production of yarns from the Textile Industry Division, Bureau of Industrial Sectors Development of the Department of Industrial Promotion and exchange rates; consumer price index and the value of textile industry exports from the Ministry of Commerce. Before investigating the models, the export data was converted from baht to dollar amounts. Thai textile products were classified into two main groups, clothing, fabric and yarn, and respectively 4 and 3 subgroups. The clothing subgroups were readymade-clothing, brassieres, braces and parts thereof, sock and tights and fabric gloves. The fabric and yarn subgroups were fabric, Man-made yarn and yarn. Comparison of the forecasts from the four techniques showed that the Box-Jenkins Techniques gave the least mean absolute percent error for most categories. However, in fabric and yarn, and fabric, regression analysis gave better results than Box-Jenkins. Based on the results of this research, models have been constructed to forecast the export value of all textile products in the above categories for 1999 and 2000. The conclusion from the models can be expressed as following: The export of clothing, readymade-clothing, sock and tights, fabric gloves, Man-made yarn and yarn combined together are expected to drop about 9.67%. The brassiere products, the fabric and yarn products, and the fabric products exports are expected to increase about 1.75%. For the past 10 years, clothing has been the main export group which are considered to be very important for building a strong Thai economy but these exports are expected to reduce the total textile exports by approximately 4.08%. This information is extremely useful for the Thai government to make critical decisions on export policy in order to maintain Thailand as a leadering textile exporting country in the future.